Studi Eksperimental Pengaruh Pemanfaatan Octane Booster Generator Gas HHO dengan Campuran Pertalite - Ethanol (E10) Sebagai Bahan BakarTerhadap Performa Mesin Yamaha Mio 155 cc - Putra, Tunas Aditya; , Ir.Sartono putro,MT (2017)
Alternative fuels in Indonesia are abundant as the depletion of fossil fuels and high demands on machine performance require further research on fossil fuel replacement resources or alternative fuels that have good quality. Use of alternative fuels as a mixture of fossil fuels within Increase the commercial octane number has been used in some developed countries. This study aims to investigate the effect of utilization of Brown gas or HHO gas and 90% - ethanol 10% (E10) Pertalite fuel mixture on the performance of four-stroke gasoline engine. The research method used is experimental method which is done by standard procedure of machine performance test. The free variable of research that is done based on engine rpm from 2000 to 9000 rpm with flowrate Brown HHO gas8,33 ml/second as octane booster injected into intake manifold and use of 90% -ethanol 10 % As fuel. The bound variables are motor power (Hp), motor torque (Nm), and specific fuel consumption (KBBS). The results of the test show that the use of 90% - ethanol blend fuel 10% ethanol (E10) - HHO gas shows the best dynotest test results where the peak power is 6.13 kW increased (7.17%) at 6500 rpm and torque 9.37 Nm Increased (7.38%) at 6500 rpm compared to 100% of the fuel consumption. While specific fuel consumption (KBBS) is best demonstrated by the use of 100% HHO-fueled 100% gasoline is 0,057 kg / kW.jam at rpm 6500 difference 11.73% compared to use of fuel of pertalite 100%.